EXPERIMENTAL STUDY OF WALL STRESS-STRAIN STATE OF A STEEL SPIRAL-FOLD SILOS (Collection of scientific works «Modern structures of metal and wood», 2023)
In the context of martial law, Ukraine's agricultural sector is suffering significant losses. By May 2022. Ukraine has already lost almost 13 million tonnes of elevator capacity, some of the grain warehouses have been completely destroyed, and some are in the occupied territories. In this regard, there is a need for elevator capacities, namely, prefabricated, cost-efficient storage capacities. Such structures are exemplified by silos. There are many design solutions for metal silos. However,  the  rising  cost  of  materials  is  causing  a  need  to  reduce  the  material  intensity  of  the structure,  which  is  encouraging  cylindrical  silo  manufacturers  to  search  for  new  types  of  shell construction. An innovative design of lightweight, industrial silos is a metal spiral-fold silo. The article describes the design of steel spiral-fold silos. The specifics of the spiral-fold silo design, which affects their stress-strain state, are analysed. The characteristics of the silo that was used  as  a  source  of  samples  for  the  experiment  are  given.  The  samples  and  equipment  for  the experimental study of a wall of a metal spiral-fold silo are considered. The stages of the experiment are described. The loading of the samples was performed by  a central bending load applied in a static mode in the range from 0 kN to 5.5 kN. To determine the relative strains, the structure was unloaded  after  each  loading  stage.  The  analysis  of  the  sample's  relative  strains  which  were measured  by AVD-4  is  made. The  character  of  interaction  and  deformation  of  the  wall  with  the folding lock is revealed. The degree of the folding lock opening was estimated. The character of work of the wall and the folding lock in the limit and non-limit states is obtained. A  comparison  of  experimental  results  with  finite  element  analysis  in  the  LIRA-SAPR software package was performed. The conclusion about the reliable operation of the wall of a spiral-fold silo under operational and increased loads is substantiated.